Produtos televisuais: trajetória e alterações de percurso - Strassburger, Damaris (2016)
The present investigation aims at examining the trajectory of televisual products that do not have, beforehand, estimated completion date, that means, for its time slot exclusion, paying special attention to the course changes realized by them, aiming at staying on air. For this purpose, the show Esquenta!, that between the years 2011, 2012 and early 2013 was broadcast by seasons, but, from May 2013 onwards, became a part of the fixed time slot of Rede Globo television network, was elected as object of study. We move from the hypothesis that many televisual shows, depending on the subgenre to which they belong, in the attempt of staying on air, operate, throughout its existence course, structural transformations and/or adopt new configurations: articulate other contexts, propose new themes, new segments, changing, if necessary, their own identity in search of constructing a more permanent television viewer. The research realized seeks, thus, to answer questions formulated about the trajectory of televisual products, inquiring when, how and why transformations of structural character are operated on a televisual product, changing its function, proposal and trajectory on the slot of a broadcaster. How do such changes affect the identity of the show and the image and brand of a television network? And what relations do such changes have with the social context? So, the main objective of the present research is to verify what strategies could be virtually employed by a televisual product, related to the subgenre auditorium show, for staying on air throughout the years. In order to meeting such broader objective, the following specifiec objectives were established: a) mapping a historic of the emergence of auditorium shows in the Brazilian televisual context; b) setting up the communicative and enunciative context of Esquenta!, from the launch of the show to the current moment, after it became a part of the fixed time slot of the broadcaster, describing its sociocultural and enunciative surroundings, production core and staff responsible for its realization; c) analyzing the intertextual relations of paradigmatic character contracted by Esquenta! with its subgenre auditorium shows; d) presenting a general setting of Esquenta!, examining the show, by seasons and emissions, regarding the adopted formats, segments, preferred themes, form of spatial, temporal and tonal structure, form of actors configuration conductor/animator, fixed participants, eventual guests, audience, etc; e) identifying structural changes by which Esquenta! went through in terms of the interests that guide the action of Rede Globo; f) examining the communicative and discursive strategies employed by the show in the configuration of its identity, image and target audience to meet its course changes and simultaneously adapt to the image and brand of Rede Globo; g) examining the intertextual relations of syntagmatic character contracted by the show with other televisual products it reclaims. Considering the issue raised and the objectives established, a discursive analysis of semiotic inspiration, of different emissions of the show, was realized.